2019
DOI: 10.26487/hebr.v3i1.1846
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Efficiency Mediation in the Effect of Banks Size on Bank Profitability in Indonesia

Abstract: The purpose of this study was to analyze the mediating role of bank efficiency in the effect of bank size on bank profitability. The research sample is 25 banks that have a minimum core capital of Rp. 5,000,000,000,000 and publish financial statements in full during 2010-2017. The data analysis technique in this study is path analysis (path analysis) with the help of AMOS software (Analysis of Moment Structure). The results of the study found that; 1) bank size has a positive and significant effect on bank eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
3
8
1
1
Order By: Relevance
“…As quoted by Ibrahim and Rizvi (2017), "we need bigger Islamic banks". This result is supported by the analysis of Amene, and Alemu (2019), Ruslan, Pahlevi, Alam, & Nohong (2019), Jaouad and Lahsen (2018), Abduh, and Idrees (2013), and Demirgüç-Kunt, and Merrouche (2010 which state that larger banks might be more efficient due to economies scale. Since the larger bank can easily diversify their assets portfolio while it reduces expenses more efficiently and effectively.…”
Section: Multivariate Results Of Mandamentioning
confidence: 72%
See 1 more Smart Citation
“…As quoted by Ibrahim and Rizvi (2017), "we need bigger Islamic banks". This result is supported by the analysis of Amene, and Alemu (2019), Ruslan, Pahlevi, Alam, & Nohong (2019), Jaouad and Lahsen (2018), Abduh, and Idrees (2013), and Demirgüç-Kunt, and Merrouche (2010 which state that larger banks might be more efficient due to economies scale. Since the larger bank can easily diversify their assets portfolio while it reduces expenses more efficiently and effectively.…”
Section: Multivariate Results Of Mandamentioning
confidence: 72%
“…Similarly, Abduh, and Idrees (2013) has found a negative relationship between bank size and performance. On the contrary, Nafti et al (2017), and Ruslan, Pahlevi, Alam, & Nohong (2019) have found that bank size has a positive and significant influence on bank profitability through bank efficiency (mediating effect). Fang, C. K. Lu, Tan, & Zhang (2019) has conducted a study in Chania and found that there is a relationship between the bank's sizes and the bank's performance.…”
Section: Review Of Literaturementioning
confidence: 97%
“…The findings of this study are in line with the findings of previous studies in the context of banks, both Islamic banks and conventional banks. Efficiency affects profitability [2], [3], [4], [5], [6], [7], [8]. Bank efficiency has a positive effect on bank profitability.…”
Section: Resultsmentioning
confidence: 99%
“…ROA is the ratio of net income divided by total assets of the bank where ROE is the ratio of net income by shareholders' equity. Ruslan et al (2019) and Robin et al (2018) point out that ROA is a measure of bank profitability which focuses on the bank's ability to earn income from its operations. ROE reflects how effectively a bank management is using shareholders' funds based on total equity (Kennedy, 2019;Ommeren, 2011).…”
Section: Datamentioning
confidence: 99%